Advanced glycation end‐products increase IL‐6 and ICAM‐1 expression via RAGE, MAPK and NF‐κB pathways in human gingival fibroblasts. (30th November 2017) - Nonaka, K.; Kajiura, Y.; Bando, M.; Sakamoto, E.; Inagaki, Y.; Lew, J. H.; Naruishi, K.; Ikuta, T.; Yoshida, K.; Kobayashi, T.; Yoshie, H.; Nagata, T.; et al.
Abstract : Background and Objectives: Diabetes mellitus (DM) is a risk factor for periodontal diseases and may exacerbate the progression of the pathogenesis of periodontitis. Advanced glycation end‐products (AGEs) cause DM complications relative to levels of glycemic control and larger amounts accumulate in the periodontal tissues of patients with periodontitis and DM. In the present study, we investigated the effects of AGEs on the expression of inflammation‐related factors in human gingival fibroblasts (HGFs) to elucidate the impact of AGEs on DM‐associated periodontitis. Material and Methods: HGFs were cultured with or without AGEs. Cell viability was examined, and RNA and protein fractions were isolated from AGE‐treated cells. The expression of interleukin (IL)‐6, intercellular adhesion molecule‐1 (ICAM‐1), and the receptor for AGE (RAGE) was investigated using reverse transcription‐polymerase chain reaction, quantitative real‐time polymerase chain reaction and enzyme‐linked immunosorbent assay, and reactive oxygen species activity was measured using a kit with 2′, 7′‐dichlorofluorescin diacetate. Human monocytic cells (THP‐1) labeled with a fluorescent reagent were co‐cultured with HGFs treated with AGEs and IL‐6 siRNA, and the adhesive activity of THP‐1 cells to HGFs was assessed. The expression of IL‐6 and ICAM‐1 was examined when HGFs were pretreated with recombinant human IL‐6, the siRNAs of RAGE and IL‐6, and inhibitors of MAPK and NF‐κB, and then cultured with and without AGEs. The phosphorylation of MAPK and NF‐κB was assessed using western blotting. Results: AGEs increased the mRNA and protein expressions of RAGE, IL‐6, ICAM‐1 and reactive oxygen species activity in HGFs, and promoted the adhesion of THP‐1 cells to HGFs, but had no effect on cell viability until 72 hours. Recombinant human IL‐6 increased ICAM‐1 expression in HGFs, while the siRNAs of RAGE and IL‐6 inhibited AGE‐induced IL6 and ICAM1 mRNA expression, and IL‐6 siRNA depressed AGE‐induced THP‐1 cell adhesion. AGEs increased the phosphorylation of p38 and ERK MAPKs, p65 NF‐κB and IκBα, while inhibitors of p38, ERK MAPKs and NF‐κB significantly decreased AGE‐induced IL‐6 and ICAM‐1 expression. Conclusion: AGEs increase IL‐6 and ICAM‐1 expression via the RAGE, MAPK and NF‐κB pathways in HGFs and may exacerbate the progression of the pathogenesis of periodontal diseases.